Clinical characteristics and resource utilization of emergency department patients with obstructive sleep apnea - Mengzhu Sun; Xingyu Zhang; Yan-Cun Liu; Jiao Pei; Hui Fan; Jianguo Guo (PLoS ONE, 2025)
Background This study investigates the differences between patients with and without obstructive sleep apnea (OSA) in U.S. emergency departments (EDs), focusing on demographics, resource utilization, clinical characteristics, and outcomes. Methods Using data from the 2016−2017 National Hospital Ambulatory Medical Care Survey Emergency Department Subfile (NHAMCS-ED), we analyzed adult ED visits. Patients were classified as having OSA based on documented diagnoses or ICD-10-CM codes. Outcomes included hospital and ICU admission rates, medical resource utilization (e.g., imaging, blood tests), and mortality. Logistic regression was used to adjust for confounders. Results OSA accounted for approximately 5,985,955 (2.8%) annual ED visits. Compared to non-OSA patients, those with OSA were more likely to be male (adjusted OR: 1.34, 95% CI: 1.14–1.57) and older, with the highest prevalence in the 60–74 age group. OSA patients were more likely to visit for respiratory (16.4% vs. 10.1%) and cardiovascular symptoms (3.5% vs. 2.1%). They required higher levels of care, with elevated hospital (30.3% vs. 13.7%, adjusted OR: 1.27, 95% CI: 1.03–1.58). Resource use was significantly higher, including blood tests (75.0% vs. 54.9%, adjusted OR: 1.58, 95% CI: 1.26–1.98) and imaging (73.1% vs. 53.9%, adjusted OR: 1.30, 95% CI: 1.07–1.59). Conclusions Patients with OSA represent a distinct subgroup in EDs, characterized by greater resource needs, higher acuity, and worse outcomes. These findings underscore the importance of optimizing care strategies for this population to reduce the clinical and economic burden.